Crystal structure of arginine methyltransferase 6 from Trypanosoma brucei. - Chongyuan Wang (PLoS ONE, 2014)
Arginine methylation plays vital roles in the cellular functions of the protozoan Trypanosoma brucei. The T. brucei arginine methyltransferase 6 (TbPRMT6) is a type I arginine methyltransferase homologous to human PRMT6. In this study, we report the crystal structures of apo-TbPRMT6 and its complex with the reaction product S-adenosyl-homocysteine (SAH). The structure of apo-TbPRMT6 displays several features that are different from those of type I PRMTs that were structurally characterized previously, including four stretches of insertion, the absence of strand β15, and a distinct dimerization arm. The comparison of the apo-TbPRMT6 and SAH-TbPRMT6 structures revealed the fine rearrangements in the active site upon SAH binding. The isothermal titration calorimetry results demonstrated that SAH binding greatly increases the affinity of TbPRMT6 to a substrate peptide derived from bovine histone H4. The western blotting and mass spectrometry results revealed that TbPRMT6 methylates bovine histone H4 tail at arginine 3 but cannot methylate several T. brucei histone tails. In summary, our results highlight the structural differences between TbPRMT6 and other type I PRMTs and reveal that the active site rearrangement upon SAH binding is important for the substrate binding of TbPRMT6.